Law No. 155 of the Year 2022 Amending Certain Provisions of Law No. 141 of teh Year 2014 Organinzing the Activity of Financing Micro, Small and Medium-Sized Enterprises = قانون رقم 155 لسنة 2022 بتعديل بعض أحكام القانون رقم 141 لسنة 2014 بتنظيم مزاولة نشاط تمويل المشروعات المتوسطة والصغيرة ومتناهية الصغر - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic